Increased Bone Mineral Density with Monthly Intravenous Ibandronate Contributes to Fracture Risk Reduction in Patients with Primary Osteoporosis: Three-Year Analysis of the MOVER Study - Hagino, Hiroshi (Calcif Tissue Int, 2014)
The relationship between gains in bone mineral density (BMD) in the hip and the incidence of vertebral fractures in the MOVER study was examined. Japanese patients from the ibandronate and risedronate treatment groups whose hip BMD had increased during the 3-year treatment period were classified into those with or without vertebral fractures. In both the ibandronate group and the risedronate group, hip BMD gains in the patients who had developed no vertebral fractures during the treatment period were greater than in the patients who developed vertebral fractures. We categorized the gains in hip BMD at 6 months into 3 groups (≤0, >0 to ≤3, and >3 %), and used logistic regression analysis to estimate odds ratios and the probabilities of incidence of vertebral fractures at 12, 24, and 36 months. The current study demonstrated that greater gains in hip BMD during the first 6 months of treatment were associated with a reduction in the risk of subsequent vertebral fractures during the duration of treatment, and suggested that measurement of hip BMD gain at that time could lead to a prediction of the risk of the future vertebral fracture incidence.